2013
DOI: 10.4103/0975-5950.117882
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of stress patterns in bone around dental implant for different abutment angulations under axial and oblique loading: A finite element analysis

Abstract: Introduction:The replacement of missing anterior teeth presents peculiar challenges to the Prosthodontist. Implants are increasingly gaining favour for the same. The morphology of existing bone in the premaxilla often dictates that implants are placed at angles that are difficult to restore with conventional abutments. However, the angulated abutments might transfer unfavourable forces to the implant or bone, thereby compromising the prognosis of the treatment. Because, it is difficult to assess the generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…The study showed that as the abutments angulation changes from 0° to 20° both compressive and tensile stresses increased, but it is within the tolerance limit of the bone. Most of studies agreed with that angled abutments result in increased stress on the implants and adjacent bone, and these increased stresses usually are within physiological tolerances [ 11 , 19 ]. Most of studies have predicted that use of angled abutments on implant results in a greater amount of stress in bone.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The study showed that as the abutments angulation changes from 0° to 20° both compressive and tensile stresses increased, but it is within the tolerance limit of the bone. Most of studies agreed with that angled abutments result in increased stress on the implants and adjacent bone, and these increased stresses usually are within physiological tolerances [ 11 , 19 ]. Most of studies have predicted that use of angled abutments on implant results in a greater amount of stress in bone.…”
Section: Discussionmentioning
confidence: 76%
“…This result suggests that angled abutments may be a suitable restorative option when implants are not placed in the ideal axial position. Bahuguna et al [ 19 ] modelled the frontal region of maxilla with a cortical layer containing an inner cancellous core. The different abutments angulations used were 0°, 10°, 15°, and 20°.…”
Section: Discussionmentioning
confidence: 99%
“…Stress distribution in FEM studies is generally interpreted as von Mises stress, which could be maximum and minimum principal stress or it could be principal strains. [38] von Mises stress is estimated in three planes, that is, x -axis, y -axis, and z -axis using a formula. [39] Validation is done by comparing the current FEM results with that of the previous studies related to a particular topic.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] In all cases, to simulate the functional forces, a 100-N force with a 30-degree angle was imposed buccolingually from long axis of each veneer. [ 26 27 ] In this software, the models for veneer and implant were designed using available references and manufacturer's instructions. [ 28 ] According to the shape of the jaw arch,[ 12 ] the number of two to four implants for reconstruction of six maxillary anterior teeth replaced, and on this basis, nine models were simulated.…”
Section: Methodsmentioning
confidence: 99%